Implementing personal software process in undergraduate course to improve model-view-controller software construction - Nachiengmai,W. (Springer Verlag, 2015)
© Springer-Verlag Berlin Heidelberg 2015. This research attempts to implement the concepts of Personal Software Process (PSP) with Model View Controller (MVC) software construction in an undergraduate software engineering course. Exercises were redesigned to support the MVC framework based on the traditional PSP exercises. The findings proposed are a guide for instructors to improving both personal and team performance in MVC software construction.